2011
DOI: 10.1002/chem.201102059
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Studies on Organic D‐π‐A Systems Containing Three‐Coordinate Boron Moieties as both π‐Donor and π‐Acceptor

Abstract: Four linear π-conjugated systems with 1,3-diethyl-1,3,2-benzodiazaborolyl [C(6)H(4)(NEt)(2)B] as a π-donor at one end and dimesitylboryl (BMes(2)) as a π-acceptor at the other end were synthesized. These unusual push-pull systems contain phenylene (-1,4-C(6)H(4)-; 1), biphenylene (-4,4'-(1,1'-C(6)H(4))(2)-; 2), thiophene (-2,5-C(4)H(2)S-; 3), and dithiophene (-5,5'-(2,2'-C(4)H(2)S)(2)-; 4) as π-conjugated bridges and different types of three-coordinate boron moieties serving as both π-donor and π-acceptor. Mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 135 publications
6
54
0
Order By: Relevance
“…The hybrid functional CAM-B3LYP is used to compute charge transfer transitions as it has the necessary physics to model charge contributions more correctly than the widely used B3LYP functional. [37] TD-DFT data are summarised in Table 4 The computed absorption maxima for 2a and 6a with similar molecular lengths agree with those observed experimentally for 2 and 6 in non-polar media. Such similarities also apply to the longer molecules, 3a, 7a, 3 and 7.…”
Section: Molecular Orbital Computationssupporting
confidence: 75%
“…The hybrid functional CAM-B3LYP is used to compute charge transfer transitions as it has the necessary physics to model charge contributions more correctly than the widely used B3LYP functional. [37] TD-DFT data are summarised in Table 4 The computed absorption maxima for 2a and 6a with similar molecular lengths agree with those observed experimentally for 2 and 6 in non-polar media. Such similarities also apply to the longer molecules, 3a, 7a, 3 and 7.…”
Section: Molecular Orbital Computationssupporting
confidence: 75%
“…20 The data summarised in Table 3 show very good agreement between the observed absorption maxima of the strong bands and the computed maxima with predicted strong bands. However, bands with lower oscillator strengths are predicted at lower energies for 6, 7, 9 and 10.…”
Section: Td-dft Computationssupporting
confidence: 57%
“…19 It was experimentally confirmed that the π-donor capacity of the 1,3-diethyl-1,3,2-benzodiazaborolyl group towards the BMes 2 -acceptor is between those of 3 methoxy-and dimethylamino-groups. 20 Benzodiazaboroles are also efficient donors when linked to the carbon atoms of carborane clusters. 25,26 In a recent paper, we reported on a series of carbazolylphenyl-and carbazolylthienylderivatives of benzodiazaboroles, 1-4, (Chart 1) where both N-atoms were substituted by electron-withdrawing pentafluorophenyl or tetrafluoropyridyl groups.…”
Section: -24mentioning
confidence: 99%
“…Titration experiments were performed with a commercially available tetrabutylammonium fluoride solution (1 M in THF). 28 NMR spectra were recorded at room temperature with a Bruker AM Avance DRX-500 spectrometer { 1 H, 11 B, 13 C} by using TMS and BF 3 ·OEt 2 as external standards. Mass spectra were taken with a VG autospec sector field mass spectrometer (Micromass).…”
Section: Methodsmentioning
confidence: 99%
“…16,[22][23][24][25][26][27] As the BMes 2 group is known as an effective acceptor (A) and the benzodiazaborolyl unit has been suggested to be a π-donor (D) 27 the novel "push-pull"-systems [D-bridge-A] with 1,4-phenylene-, 4,4'-biphenylene-, 2,5-thiophene-and 5,5'-dithiophene-scaffolds (I-IV, Chart I) have been investigated recently. 28 Photophysical studies on these compounds reveal blue-green fluorescence and Stokes shifts for the first three representatives of 7820-9760 cm -1 in THF, whereas the Stokes shift for the last compound is significantly smaller (5510 cm -1 in THF). For comparison with closely related derivatives 3 and V-X, the cyano compound 5 was synthesized here by the lithiation of 4-cyanophenylacetylene 4 31 in THF and the subsequent treatment of the organolithium species with an equimolar amount of 2-bromo-1,3,2-benzodiazaborole 1.…”
Section: Introductionmentioning
confidence: 97%